HUBUNGAN PENGGUNAAN INSTRUMEN PENILAIAN KEMAMPUAN PEMECAHAN MASALAH DENGAN EFIKASI DIRI PESERTA DIDIK PADA MATERI LAJU REAKSI - Nurbaiti; Maria Erna; Dedi Futra (Postgraduate, University of Mataram, 2023)
This study aims to find out how the relationship between students' self -efficacy and self -efficacy in the reaction rate material. This type of research is an experimental study with pretest-posttest design. The sampling technique in this study was a random sampling technique, namely by choosing 3 high school (SMA) in Bengkalis Regency, namely SMA Negeri 2 Mandau, 8 Mandau State High School, and IT Al-Kautsar State High School. The correlation test was carried out to find out whether between two variables there was a relationship, and if there was a relationship, how the direction of the relationship and how much the relationship was. Based on the results of the correlation test that there is a positive correlation between the ability to solve problems and self -efficacy in students in high school, medium and low.